Nichtinvasive Beatmung bei Kindern mit akuter respiratorischer Insuffizienz - Fuchs, H. (Notf Rett Med, 2017)
Noninvasive ventilation (NIV) may be used to treat pediatric acute respiratory failure. Recent improvements in ventilator technology and availability of nasal and full face masks for infants and children have simplified the use of NIV even in the smallest children. Mainly patients with hypercapnic respiratory failure may benefit from noninvasive ventilation. There is some evidence available that supports the use of NIV in viral bronchiolitis, asthma and acute on chronic respiratory failure in patients with neuromuscular or chronic pulmonary disease. Furthermore, noninvasive ventilation is beneficial during prolonged weaning from invasive ventilation and to treat upper airway obstructions. Children suffering from hypoxic respiratory failure, such as community-acquired pneumonia and acute respiratory distress syndrome do not benefit from NIV. Due to possibly relevant side effects and the possibility of rapid deterioration in gas exchange in failure of NIV, invasive ventilation should be readily available; therefore, treatment with noninvasive ventilation for acute respiratory failure in children should be initiated on the pediatric intensive care ward.